Systematics of the Ameerega rubriventris complex (Anura: Dendrobatidae) with descriptions of two new cryptic species from the East-Andean versant of Peru - Brown, Jason L.; Siu-Ting, Karen; Von May, Rudolf; Twomey, Evan; Guillory, Wilson X.; Deutsch, Michael S.; Chávez, Germán (Zootaxa, 2019)
We describe two new species of poison frog from central and southern Peru that have been referred to as Ameerega picta, A. hahneli, or A. altamazonica throughout the past thirty years. Our phylogenies generated with genomic data provide strong support that the two new species are successive sisters to two described taxa, A. rubriventris and A. altamazonica, and collectively comprise the Ameerega rubriventris complex. The first new taxon, Ameerega panguana sp. nov., can be distinguished from all other Ameerega by its combination of a unique white venter and an advertisement call of 1–2 notes per second. The second new taxon, Ameerega imasmari sp. nov., is the only cryptically colored Ameerega species that is disttributed across the Fitzcarrald Arch in Southern Peru which possesses a ‘peep’ advertisement call consisting of 3–4 notes per second and a dominant frequency of 4.3–4.5 kHz. Within the Ameerega rubriventris complex, we observed differences between species in their ventral coloration, tympanum diameter, and call, which suggest that these taxa are reproductively isolated from each other.